Free Vibration of Laminated Composite Plates with Cut-Out - Varun Kumar Sikka1, Shailesh (International Journal of New Media Studies: International Peer Reviewed Scholarly Indexed Journal, 2023)
The laminated composite plate are basics components of structure used in various field of engineering such as turbine blades, airplane wing and helicopter blades as well as many others in civil, automotive and ship industries etc. due to their excellent high stiffness to weight ratio and strength to weight ratio. Cut-outs are provided in structure for venting, reducing weight and passage of electrical wires. Most of the structures are subjected to severe dynamic loading during their service life.